Family Perspectives on Integrated Employment for Adults with Intellectual and Developmental Disabilities. (March 2018) - Gilson, Carly B.; Carter, Erik W.; Bumble, Jennifer L.; McMillan, Elise D.
Families are essential partners in efforts to elevate the employment outcomes of adults with intellectual and developmental disabilities (IDD). We examined the employment-related expectations, preferences, and concerns of 673 parents and other family members of adults with IDD. Participants prioritized paid integrated employment over sheltered options, and such perspectives were strongly associated with the recent employment status of their family member with IDD. In addition, they valued qualitative dimensions of a potential workplace (e.g., personal satisfaction, social interaction opportunities) more highly than prevailing employment metrics (e.g., rate of pay, hours per week, benefits). Multiple factors informed the views of parents and other family members regarding integrated employment and the extent to which their family member with IDD had been employed previously in the community. We offer recommendations for research, practice, and systems change efforts aimed at raising expectations for and access to integrated employment for adults with IDD.